Geographical determinants and hotspots of out-of-school children in Nigeria - Adeleke Richard; Alabede Opeyemi (De Gruyter, 2022)
In Nigeria, children lack access to primary school education, and this hinders their social, cognitive, emotional, and physical skills' development. With one in every five of the world's out-of-school children in Nigeria, achieving universal primary education by 2030 remains a challenge. Several studies have investigated the factors that have led to an increase in out-of-school children (OOSC); however, these studies are based on individual level and household predictors with little evidence on the geographical determinants. Hence, this study examines the relationship between OOSC and the socio-economic attributes of the geographical location where they reside. Findings of the spatial analysis show that Sokoto, Zamfara, Yobe, Taraba, and Plateau are the hotspots of out-of-school children. The result further reveals that there is spatial variation in the predictors of out-of-school children in the country. Poverty and internally generated revenue (IGR) predict more cases of school non-attendance in northern Nigeria while foreign direct investment determines the number of children that are out-of-school in the southern region. The study recommends spatially explicit policies to reduce the number of OOSC in Nigeria.